Cranial Bone Changes Associated With Intracranial Hypertension in Apert Syndrome: Insights for Early Surgical Intervention - Diego A. Gomez, BS; Isabelle J. Meredith, BS; Skyler K. Palmer, BS; Marius George Linguraru, DPhil; David Y. Khechoyan, MD; Phuong D. Nguyen, MD; Brooke French, MD; Antonio R. Porras, PhD (Plastic and Reconstructive Surgery, Global Open)
Background:. The presence of intracranial hypertension (ICH) is a key consideration in the surgical management of Apert syndrome (AS). However, cranial signs indicative of ICH are underexplored. We used routinely acquired computed tomographic images to deliver the first quantitative assessment of localized cranial bone and volumetric anomalies associated with ICH in children with AS. Methods:. Children with AS with preoperative computed tomographic scans were retrospectively identified at 2 institutions. Patients with preceding craniofacial intervention were excluded. Local cranial bone thickness, cranial density, and intracranial volume (ICV) anomalies were compared among 3 cohorts: AS, nonsyndromic bicoronal craniosynostosis (NSBC), and normative patients without cranial pathology. Adjustments were made for age and sex. Results:. A total of 671 patients were included (16 AS, 631 normative, and 24 NSBC). All patients with AS displayed bicoronal suture involvement, and 9 showed additional suture fusions. Patients with AS had significantly increased cranial bone thickness and total ICV, as well as significantly decreased cranial bone density and occipital volume compared with the normative cohort. Compared with NSBC, patients with AS demonstrated greater cranial density loss and ICV increase under the frontal and parietal bones, with no significant differences in the occipital region. Conclusions:. Before surgical intervention, children with AS exhibit distinct cranial adaptations to chronic ICH, characterized by increased ICV and decreased cranial bone density, suggesting that earlier surgical intervention may be necessary to prevent the effects of chronic ICH. Furthermore, the predominant volume restriction in the occipital region supports posterior expansion as the initial intervention.